Predictors of treatment response in cirrhotic patients with overt hepatic encephalopathy (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Hepatic encephalopathy (HE) is a frequent complication and one of the most debilitating manifestations of liver cirrhosis, which negatively impacts patient survival. This study aims to identify the factors influencing the treatment response in patients with liver cirrhosis and HE.Method: This was a prospective observational study conducted from July 2019 to June 2020 in a tertiary referral center of Nepal. The ethical clearance was obtained from the Institutional Review Board of the center (Reference No. 46/076/77). Patients with Liver cirrhosis with HE grade II or more were included. Standard medical therapy for HE was given to all the patients, and treatment response for the first five days post admission was recorded. The response was categorized as good response, no response and deterioration, based on improvement or deterioration of patient`s symptoms or changes in West Haven criteria.Result: In this study total 78 patients were enrolled and included in the final analysis. The mean age was 50.17± 10.36 years and 63(80.76%) were male. Alcohol was the etiology of cirrhosis in 62(79.5%). Seventy two (92.3%)  patients had good response to the treatment, 3(3.8 %) of patients had no response and rest 3(3.8%) deteriorated. On logistic regression, high creatinine, high bilirubin and low serum protein were the predictors of non-response to standard therapy (p